2×2 Microfluidic Optical Switch with Ferromagnetic Fluid Drive - SHI Zheng; WAN Jing; YU Tingjie; ZHOU Rui; CHEN Jiansong (Guangtongxin yanjiu)
【Objective】Common optical switches are usually polarization sensitive or have complex structures, the article proposes a 2×2 microfluidic optical switch.【Methods】The optical switch proposed in this article employs a waveguide structure. It utilizes microfluidic driving technology based on magnetic fluids, along with trace amounts of liquid and air, to achieve optical path selection and switching functions for the optical switch. The transmission characteristics of optical switch are studied and discussed, and the structure of optical switch is optimized.【Results】The results show that the insertion losses at two output ports of optical switch are 0.42 and 0.20 dB, and the crosstalk are -24.13 and -42.63 dB, respectively.【Conclusion】The proposed 2×2 microfluidic optical switch has simple structure and is not sensitive to polarization. It also has lower insertion loss and crosstalk than common optical switches. It can be used as the switching core for building Optical Cross Connect (OXC) equipment to realize the fault protection function of the optical network.